Penerapan Sanksi Pidana Kepada Anak Penyalahgunaan Narkotika (Studi Kasus PSBR Hiti-Hiti Hala-Hala) - Magdalena Yuni Tahalele; Juanrico Alfaromona Sumarezs Titahelu; Erwin Ubwarin (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Narcotics abuse is a problem that occurs both nationally and internationally and has not been resolved to date. Narcotics abuse can be felt by all persons regardless of ethnicity, race and religion, including children. The purpose of this study was to find out and provide an overview of the application of this form of coaching to children who abuse narcotics at PSBR & ABH Hiti-Hiti Hala-Hala. The type of research used in this research is empirical legal research. By using the method of data collection techniques in the form of field studies in which there are interviews in oral form by asking several questions to the informants related to the problem under study and conducting literature studies which use laws and regulations, legal journals, encyclopedias relevant to the research material. From the data that has been collected from the results of research, in this case interviews with relevant sources as well as collection from several literatures, laws, and books related to these problems. Then it will be analyzed descriptively to provide an overview of the subject of the results of the research conducted. The results of this study concluded that Narcotics are drugs derived from synthetic and semi-synthetic plants which cause a decrease in consciousness and lead to dependence. Article 1 point 1 Law No. 35 of 2009 concerning the abuse of narcotics. The abuse of narcotics by minors can certainly affect the mental health of children, physically interfere with children, to the point of dependence and addiction, so that children become addicted. This is because children are unstable so they are easily influenced and guidance and rehabilitation must be carried out for both users and dealers. But the fact is that, in carrying out criminal applications to children who abuse narcotics. Children who abuse narcotics are placed in the Hiti-Hiti Hala-Hala Social Institution for Youth and Children in Conflict with the Law (PSBR&ABH).